Characterization of eight species of Aloe (Asphodelaceae) from the nucleolar organizing region - Sánchez, Ysbelia (2018)
Nucleolar organizing region of eight species of Aloe was analyzed in somatic metaphases and interphase nuclei. All species showed a uniform 2n=14, with eight large chromosomes and six small chromosomes. Satellites were observed on the long arm of one or two pairs of large chromosomes and/or on the short arm of one of the small pairs. The silver-stained nucleolus organizing regions were located on the subtelomeric region of the long arm of one or two pairs of large chromosomes, except for Aloe dichotoma and Aloe maculata, which the AgNORs were located at a short arm of one of their small chromosomes. In most studied species, the active AgNOR number was four. However, this number changing from one to eight. For all species, the interphase number of nucleoli can be one or two, while, in Aloe excelsa, this number can be changing from one to eight. Polymorphism of active AgNORs and the number of interphase nucleoli were revealed, except for Aloe petricola, which active AgNORs were located only in the subtelomeric regions at the long arm of one of the L2 chromosomes, as well as in the L4 pair, which is agreement with the maximum number (three) of interphase nucleoli.